Designing of milling tool spindle (Bangladesh Journal of Scientific and Industrial Research, 2018)
Analysis of chatter stability in an end milling process is quite cumbersome because of the inaccurate knowledge in the spindle’s geometrical design, position of the bearings and several issues related to the spindle structure. The effective position of bearings of the spindle plays a key role in investigating the self-excited chatter vibrations, which requires an accurate transfer function at the most flexibility region of the spindle tool structure. The present work focuses on the development of a novel method of measuring the spindle vibration responses experimentally using sine sweep tests for a CNC end milling machine tool. Using these model data, an analytical model of the spindle is estimated by considering the bearing span as a design variable. Trial runs are conducted until the convergence between the identified transfer function from the model and that from experiment is achieved. The final model of the spindle system is then applied with time-varying cutting forces so as to obtain the process stability.Bangladesh J. Sci. Ind. Res.53(3), 191-198, 2018